Knowledge, Awareness and Perception Regarding Importance of Primary Teeth among Parents Visiting Dental OPD, BPKIHS, Dharan, Nepal - Dali, Mamta; Koirala, Bandana; Shrestha, Sneha (Birat Journal of Health Sciences, 2019)
Introduction: Oral health knowledge and awareness among parents is an integral component of preventing dental caries among children. Objective: The purpose of this paper is to assess the parent’s knowledge, awareness and perception regarding the care of primary teeth attending the Dental OPD, BPKIHS, Dharan, Nepal. Methodology: A questionnaire based survey was conducted among 200 parents in randomly selected manner. Results: The data was analyzed using SPSS software version 12.0. Only 54% of the parents were aware of the importance of primary teeth in children and 82% understood that untreated caries in primary dentition can have effects on general health of children. Approx 82% parents were aware of pediatric dentist and majority felt that they are the right person to contact when dental problems occur in children. Surprisingly only 57% of parents were aware of the preventive role of fluorinated tooth in dental caries. A majority of parents assume that filling is the appropriate treatment option for caries in children rather than extraction and 40.5% felt that premature primary teeth extraction will results in malalignment of permanent teeth. A very negative response was obtained regarding routine dental visit to pediatric dentist. Majority (61%) visited only when dental problems occurred whereas 12-16% answered they visit in every 6 months or once in a year. Conclusions: We concluded that knowledge, awareness and perception of parents regarding importance of primary teeth were inadequate. There is an immediate need to cultivate and reinforce positive attitudes among parents and substantially raise their dental awareness through child dental health oriented programs.